THE REPRESENTATION OF PATRIARCHAL IDEOLOGY IN AMY POEHLER'S AMY POEHLER'S MOVIE "MOXIE" - Khaerati, Andi Miftahul; Iskandar, Iskandar (Journal of English Literature and Linguistic Studies, 2023)
Patriarchy which is a social system occurs when there is gender inequality where men have more influence and power over women. The researchers analyze the types of patriarchal structures by using Sylvia Walby’s (1990) theory and the struggle of female characters against patriarchy by using Simone de Beauvoir’s (2010) theory. These theories were chosen by the researchers because there has not been a study that analyzes using the theory from Sylvia Walby and Simone De Beauvoir in “Moxie” movie. This study aims to examine the types of patriarchal practices depicted in the film “Moxie” and the researchers want to analyze the female character’s struggle against patriarchy in the film “Moxie”. The qualitative descriptive method is the method that researchers use in this study. This research produced several findings. Female characters experience some discrimination from male students and even their principals. Patriarchal culture makes male students more authority over girls. Female students experience patriarchal forms of cultural structure, sexuality, violence, and the state. Vivian as the main character struggles with her friends against the unfair system that exists in her school which prioritizes boys over girls. Through the feminist movement, Vivian created zines entitled “Moxie” in which each zine contains different patriarchal topics such as drawing stars and hearts on hands as symbols of resistance and uploaded in the media using hashtags. Furthermore, the form of protest was by inviting them to use tank tops at school due to discriminatory treatment by the school principal. They also created a campaign to support Kiera as a soccer captain in order to get a scholarship and actualize themselves by showing their abilities and talents. In addition, they try to be themselves by having differences.Keywords: “Moxie” movie, Patriarchy, Women Struggles, Discrimination.